2007
DOI: 10.1002/cmdc.200700071
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Metabolically Stabilized Cyclopentyl Trisphosphate Analogues of Dmyo‐Ins(1,4,5)P3

Abstract: We describe the synthesis of four novel metabolically stabilized analogues of Ins(1,4,5)P(3) based on the known cyclopentane pentaol tris(phosphate) 2: tris(phosphorothioate) 3, tris(methylenephosphate) 4, tris(sulfonamide) 5, and tris(sulfate) 6. Of these analogues, only the tris(phosphorothioate) 3 and parent tris(phosphate) 2 bound to the type I InsP(3)R construct. In addition, both the tris(phosphorothioate) 3 and parent tris(phosphate) 2 elicited calcium release in MDA MB-435 breast cancer cells. The Ins(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Prestwich et al has reported the sulfate-and sulfamate-containing cyclopentyl InsP 3 derivatives 56 and 57. 93 These compounds were shown not to bind InsP 3 receptors, which is consistent with the data of Westerduin et al 92 Although some of these compounds show no activity at their target receptors, the data obtained are collectively useful in determining the subtle structure-activity relationships of compounds that act at the InsP 3 receptors.…”
Section: Boranophosphatessupporting
confidence: 82%
“…Prestwich et al has reported the sulfate-and sulfamate-containing cyclopentyl InsP 3 derivatives 56 and 57. 93 These compounds were shown not to bind InsP 3 receptors, which is consistent with the data of Westerduin et al 92 Although some of these compounds show no activity at their target receptors, the data obtained are collectively useful in determining the subtle structure-activity relationships of compounds that act at the InsP 3 receptors.…”
Section: Boranophosphatessupporting
confidence: 82%
“…In addition, it has been reported that structural differences in the suppressor domains contribute to functional diversity in ligand sensitivity among IP 3 R isoforms (20), assuming that the ligand-binding properties of the LIBRAv series reflect this feature of IP 3 R isoforms. We previously reported a method using LIBRA for determining IP 3 R ligands (21), and we identified novel ligands of IP 3 Rs from newly synthesized cyclopentane derivatives (22). This method could be extended easily for identifying subtype-specific ligands of IP 3 Rs by using a series of new LIBRAv variants.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we demonstrated that PtdIns(3)PT had reduced binding activity for cognate PtdIns(3)P-selective FYVE and PX domain binding proteins, which was attributable to reduced H-bonding (18). We also observed that a PT analogue of PtdIns(5)P was a long-lived agonist for chromatin remodeling (19), and a tris(PT) cyclopentyl analogue (20) of Ins(1,4,5)P 3 was a long-lived agonist activities for the IP 3 receptor. We hypothesized that a 5-PT and 5-MP analogues of PtdIns(3,4,5)P 3 could be either antagonists or long-lived PtdIns(3,4,5)P 3 agonists, as they would be more slowly dephosphorylated by the 5-phosphatase SHIP and could potentially block the normal receptor-mediated signaling involving PtdIns(3,4,5)P 3 .…”
Section: Introductionmentioning
confidence: 78%